Toxicological Evaluation of 2-Bromo-2-nitropropane-1, 3-diol as a Preservative in Fresh Aloe Gel - Satayavivad, Jutamaad; Bunyapraphatsara, Nantavan (Journal of Basic and Applied Pharmacology, 2015)
Toxicological studies of 2-bromo-2-nitropropane- J, 3-diol (BND) as a preservative in fresh aloe gel has been conducted. The results of these studies revealed that BND at the recommended dose when used alone is effective and safe as reported by the manufacturer. The LD50 of BND when it was given intraperitoneally is in the same range as previously reported by the other investigators. However, the aloe gel containing BND exhibited higher toxicity than BND or fresh aloe gel itself. The toxic effects are as follow: the irritation of rabbit skin and the abnormal formation of ligament in the peritoneal cavity leading to the attachment of internal organs to the peritoneal wall. It is interesting to find out that neither BND nor fresh aloe gel produces the abm1e toxic effects. The mechanisms underlied these toxic effects need further studies.